2010
DOI: 10.1007/s12311-010-0161-1
|View full text |Cite
|
Sign up to set email alerts
|

High Transgene Expression by Lentiviral Vectors Causes Maldevelopment of Purkinje Cells In Vivo

Abstract: Lentiviral vectors are promising as gene-transfer vehicles for gene therapy targeted to intractable brain diseases. Although lentiviral vectors are thought to exert little toxicity on infected cells, the adverse influence of viral infection on vulnerable developing neurons has not been well studied. Here, we examined whether lentiviral vector infection and subsequent transgene expression affected the morphological and functional maturation of vigorously developing cerebellar Purkinje cells in vivo. Lentiviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…We have also verified that this injection method is applicable to neonatal pups and mature mice (Fig. 2c) (Sawada et al, 2010;Torashima et al, 2006a;Torashima et al, 2006b).…”
Section: A Methods That Enables Efficient and Widespread Gene Deliverysupporting
confidence: 62%
“…We have also verified that this injection method is applicable to neonatal pups and mature mice (Fig. 2c) (Sawada et al, 2010;Torashima et al, 2006a;Torashima et al, 2006b).…”
Section: A Methods That Enables Efficient and Widespread Gene Deliverysupporting
confidence: 62%
“…However, a recent study by Hyman and colleagues reported a similar toxicity for the three variants (WT, S129D and S129A) (McFarland et al, 2009). As mentioned above, the results from this study might be biased by co-expression of GFP and a-syn (Baens et al, 2006;Sawada et al, 2010;Ulusoy et al, 2009). …”
Section: Does Phosphorylation Enhance or Protect Against A-syn Toxicity?mentioning
confidence: 83%
“…The discrepancy with the previous two models might be due to the fact that McFarland et al (2009) used a bi-cistronic mRNA to co express a-syn and green fluorescent protein (GFP), which may lead to lower expression of a syn compared to classical monocistronic RNA. Recent reports suggest neuronal toxicity associated with AAV-mediated over-expression of GFP in the substantia nigra, which could mask the differences in terms of neuronal loss caused by a-syn and the two S129 mutants (Baens et al, 2006;Sawada et al, 2010;Ulusoy et al, 2009). An additional contribut ing factor might be the fact the immunohistological analysis was carried out 6 weeks after virus injec tion, compared to 8 weeks in the studies by Azeredo da Silveira et al (2009) and Gorbatyuk et al (2008).…”
mentioning
confidence: 99%
“…Lentiviral vectors were designed to express EGFP under the control of a PC-specific promoter, L7-4N. The L7-4N promoter is a fusion promoter consisting of a minimal CMV sequence and a truncated (1 kb) PC-specific L7 promoter (Sawada et al, 2010). It exhibits much greater transcriptional activity than the original L7 promoter without compromising PC specificity (H. H., unpublished observation).…”
Section: Methodsmentioning
confidence: 99%